1993
DOI: 10.1002/1097-0142(19930101)71:1<257::aid-cncr2820710139>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-cell lymphoma in childhood and adolescence a clinicopathologic study of 22 patients

Abstract: Background. Peripheral T‐cell lymphoma (PTCL), although the most common T‐cell lymphoma in adults, is relatively rare in childhood, and only small series have been reported. Methods/Results. Twenty‐two cases of PTCL were studied that occurred in patients 18 months to 20 years of age. Nine were seen when the condition was diagnosed, and the other 13 were referred after they had relapses. The stage at diagnosis was I or II (45%), III (41%), and IV (14%). Patients with Stage IV disease were younger than those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…How the resulting NPM-ALK chimeric protein is related to tumorigenesis has yet to be determined. Although early reports suggested that the t(2;5) translocation might be unique to a morphologic entity of ALCL [27][28][29], more recently it has been shown that the translocation is not limited to cases with typical anaplastic morphology, and is in fact present in lympho-mas with a wide morphologic spectrum, including monomorphic, lymphohistiocytic, small cell-predominant, neutrophil-rich, sarcomatoid, and Hodgkins-like subtypes [8,13,15,16,24,25]. In our study the majority of tumors (two-thirds) were of T-cell or null-cell immunophenotype.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…How the resulting NPM-ALK chimeric protein is related to tumorigenesis has yet to be determined. Although early reports suggested that the t(2;5) translocation might be unique to a morphologic entity of ALCL [27][28][29], more recently it has been shown that the translocation is not limited to cases with typical anaplastic morphology, and is in fact present in lympho-mas with a wide morphologic spectrum, including monomorphic, lymphohistiocytic, small cell-predominant, neutrophil-rich, sarcomatoid, and Hodgkins-like subtypes [8,13,15,16,24,25]. In our study the majority of tumors (two-thirds) were of T-cell or null-cell immunophenotype.…”
Section: Discussionmentioning
confidence: 60%
“…Our results concur with recent suggestions that primary pediatric LCL with ALK protein expression and/or the t(2;5) translocation appears to represent a distinct pathologic entity occurring in young patients with co-expression of T-cell markers, EMA, and CD30. Recent investigators have emphasized the difficulty of using subjective morphological criteria such as anaplasia to define lymphoma subtypes [24], and it has become apparent that tumors in the ALCL category can have a varied morphologic appearance [8,13,15,16,24,25,38]. Furthermore, some authors have chosen to exclude B-cell tumors from the ALCL category [18,23,26], whereas others have not [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperleucocytosis with circulating abnormal small lymphoid cells has occasionally been reported in peripheral T‐cell lymphoma (Weisenburger et al , 1985). However, we suspect that in the study by Gordon et al (1993) on peripheral T‐cell lymphoma in childhood and adolescence, the three patients with leucocytosis (two of whom showed circulating lymphoma cells) were in fact affected by the small cell variant of ALCL. Indeed, until recently, some cases of small cell variant of ALCL were misdiagnosed as peripheral T‐cell lymphoma.…”
Section: Discussionmentioning
confidence: 98%
“…Skin involvement in T/NK‐cell lymphoma is frequent. Peripheral T/NK‐cell lymphomas (PTCL) are characterised by a mixture of small and large atypical lymphoid cells and express CD3 and either CD4 or CD8 13 but do not express CD30 or ALK‐1 that characterise anaplastic large cell lymphoma. A wide variety of histological subtypes have been recognised, the most common being PTCL not otherwise specified (NOS) 14.…”
Section: Discussionmentioning
confidence: 99%